The Trend of Bacterial Nanocellulose Research Published in the Science Citation Index Expanded From 2005 to 2020: A Bibliometric Analysis - Ho, Yuh-Shan; Fahad Halim, A. F. M.; Islam, Mohammad Tajul (Frontiers in Bioengineering and Biotechnology, 2022)
To gain insight into the trend of bacterial nanocellulose research, a bibliometric analysis was performed using the Science Citation Index Expanded database from 2005 to 2020. The study concentrated on the publication's performance in terms of annual outputs and citations, mainstream journals, categories of the Web of Sciences, leading countries, prominent institutions, and trends in research. Current research priorities and future trends were analyzed after summarizing the most commonly used keywords extracted from words in the paper title analysis, authors’ keyword analysis, and KeyWords Plus. The findings revealed that the annual output in the form of scholarly articles on bacterial nanocellulose research steadily increased during the first quartile of the study period, followed by a very rapid increase in the last 5-years of the study. Increasing mechanical strength would remain the main future focus of bacterial nanocellulose research to create its scope in different field of applications.